2018
DOI: 10.3389/fneur.2018.00720
|View full text |Cite
|
Sign up to set email alerts
|

Drug Seeking and Relapse: New Evidence of a Role for Orexin and Dynorphin Co-transmission in the Paraventricular Nucleus of the Thalamus

Abstract: The long-lasting vulnerability to relapse remains the main challenge for the successful treatment of drug addiction. Neural systems that are involved in processing natural rewards and drugs of abuse overlap. However, neuroplasticity that is caused by drug exposure may be responsible for maladaptive, compulsive, and addictive behavior. The orexin (Orx) system participates in regulating numerous physiological processes, including energy metabolism, arousal, and feeding, and is recruited by drugs of abuse. The Or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 198 publications
(245 reference statements)
1
15
0
Order By: Relevance
“…Although timing morphine conditioning with periods of vigilance did not alter morphine-induced drug seeking as measured using the CPP paradigm (Fig. 5 F ), our electrophysiological findings, and previously published studies from others, suggest that morphine-induced PVT alterations may impact reward-seeking behaviors (Matzeu et al, 2014, 2016; Matzeu and Martin-Fardon, 2018). For example, previous studies have shown that increases in PVT glutamatergic transmission in the nucleus accumbens induces aversion and blocks seeking for natural rewards (Zhu et al, 2016; Do-Monte et al, 2017), while decreasing PVT glutamatergic transmission in the accumbens increases seeking to natural rewards and increases food consumption (Do-Monte et al, 2017; Reed et al, 2018).…”
Section: Discussionsupporting
confidence: 58%
“…Although timing morphine conditioning with periods of vigilance did not alter morphine-induced drug seeking as measured using the CPP paradigm (Fig. 5 F ), our electrophysiological findings, and previously published studies from others, suggest that morphine-induced PVT alterations may impact reward-seeking behaviors (Matzeu et al, 2014, 2016; Matzeu and Martin-Fardon, 2018). For example, previous studies have shown that increases in PVT glutamatergic transmission in the nucleus accumbens induces aversion and blocks seeking for natural rewards (Zhu et al, 2016; Do-Monte et al, 2017), while decreasing PVT glutamatergic transmission in the accumbens increases seeking to natural rewards and increases food consumption (Do-Monte et al, 2017; Reed et al, 2018).…”
Section: Discussionsupporting
confidence: 58%
“…A recent body of literature also supports a role for the Hct/ OX system in a number of behaviors relevant to AUD including reward/motivated behavior [39,40], addiction [41][42][43], feeding, and energy metabolism (for review see [44]). There are also data to suggest that there is specificity with regard to Hct/Ox receptor signaling and these target behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that the role of orexin in mediating such behaviors is, in part, localized to the PVT (Li et al, 2011;Martin-Fardon & Boutrel, 2012;James & Dayas, 2013;Matzeu et al, 2014;Matzeu et al, 2016;Matzeu & Martin-Fardon, 2018), which receives dense orexinergic projections .…”
Section: Introductionmentioning
confidence: 99%